Single-Dose Indigenous Liposomal Amphotericin B in the Treatment of Indian Visceral Leishmaniasis: A Phase 2 Study - Sundar, Shyam; Singh, Anup; Rai, Madhukar; Chakravarty, Jaya (The American journal of tropical medicine and hygiene, 2015)
Liposomal amphotericin B is an effective and safe alternative for the treatment of visceral leishmaniasis in the Indian subcontinent. In this study, we used a higher-dose regimen of an indigenously manufactured liposomal amphotericin B (FUNGISOME; L-AmBL), which was intended to improve the efficacy in terms of long-lasting cure rate. Thirty men and thirty women between 12 and 60 years old with parasitologically confirmed visceral leishmaniasis were enrolled in two cohorts of 15 patients each. Subjects in cohort I were administered one dose (10 mg/kg body weight) of L-AmBL intravenously. After the safety at this dose was confirmed in cohort I, patients were recruited in cohort II. They received one infusion of an escalated dose (15 mg/kg body weight). The safety of these two doses was evaluated over a period of 30 days, and efficacy was assessed for initial cure at day 30 and definitive cure at 6 months. FUNGISOME was found to be safe, with an initial cure rate of 100% at day 30 and a definitive cure rate of 93.3% at the 6-month follow-up in both the cohorts.